The Pattern of Trunk Movements in Children with Cerebral Palsy: A Systematic Review - Meysam Roostaei; Shiva Abedi; Toktam Mazaheri (Vesnu Publications, 2016)
Introduction: Cerebral palsy is a nonprogressive disorder which results in physical and performance abnormalities. More than half of the children with cerebral palsy can walk independently, but the pattern of walking in the majority of these children is abnormal. Since the trunk is located in the center of the body, it plays a crucial role in status control and balance regulation. Thus, the aim of the present systematic review was to identify trunk movement patterns in children with cerebral palsy according to the type and severity of cerebral palsy and manner of trunk movement effects on motor control. Materials and Methods: PubMed, Google Scholar, Scopus, ProQuest, and Web of Science were searched using the keywords "gait" and "trunk" in combination with "cerebral palsy" for relevant papers published from the inception of the search engines until March 2015. The search process was conducted independently by two authors. The PEDro scale was used for assessment of the quality of the articles and CEBM Levels of Evidence Scale was used for grading evidence levels. Results: According to the inclusion and exclusion criteria, 5 articles were selected. The articles had moderate to low quality. All articles reported that increase in trunk movements were compatible with increase in severity of cerebral palsy. These movements can be considered as compensatory movements or deficit in motor control. Conclusion: Trunk movement range increases in relation to severity of cerebral palsy; however, further studies are required to determine the pattern of this increase in relation to type and severity of cerebral palsy. Moreover, the question still remains whether trunk movements should be regarded as compensatory movements or defects.